2023
DOI: 10.1371/journal.pone.0295670
|View full text |Cite
|
Sign up to set email alerts
|

HBV prevalence in Sub-continental countries: A systematic review and meta-analysis

Sam Hogan,
Andrew Page,
Sameer Dixit
et al.

Abstract: Background Hepatitis B virus (HBV) is a major source of disease burden worldwide, with an estimated 296 million individuals living with infections worldwide. Although vaccine programs exist to control infections, certain sub-populations around the world continue to have very high prevalence of HBV infection. Methods A systematic search of studies of HBV published after 2010 was conducted for India, Pakistan, Bangladesh, Nepal, Sri Lanka and Bhutan. Each paper was independently screened for risk of bias and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In contrast, the prevalence of CHB is much lower in the general population in India. For example, a study from Punjab reported a prevalence of 1.4%, while the overall prevalence for India has been estimated to be 3% [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prevalence of CHB is much lower in the general population in India. For example, a study from Punjab reported a prevalence of 1.4%, while the overall prevalence for India has been estimated to be 3% [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%